"Here Comes the Junkies, " Opioid Replacement Therapy in Rural Australia. Issue 1 (January 2021) - Opie, Cynthia Ann; Wood, Penelope; Haines, Helen Mary; Franklin, Richard C.
Abstract: Background: Opioid replacement therapy (ORT) offers a harm minimization approach and is the mainstay treatment option for opioid dependence in Australia. Recovery is known to be complicated because of service access, cost, workforce availability, privacy, stigma, and discrimination. Rural living is considered to magnify each complication of recovery, yet little is understood about how opioid dependence recovery is experienced in rural Australia. This study aimed to explore the lived experience of people receiving ORT in rural Australia and describe impediments to recovery. Methods: In this qualitative study design, all outpatients enrolled in ORT at two rural Australian sites were invited to participate. Six volunteers from each site participated in a semistructured interview (eight men, four women; mean age = 44.8 years). Results: The participants had completed 3 years of secondary school education on average. Four major themes emerged: reinvention, restriction, employment, and reconnection. Small communities increased the likelihood of ORT participants knowing people both directly and indirectly, affecting their ability to reconstruct an identity. Lived distance from prescribers and dosing points dictated daily activity, including opportunities to seek and maintain employment. Rural ORT treatment seekers indicated that geographical displacement and separation from family, the people they needed to reconnect with, were challenging. Conclusion: Rural people engaged in ORT require positive reinforcement from service providers, enabling identity reinvention and disconnection from the drug-seeking world. Acknowledging underlying trauma and supporting reconnection with loved ones may foster positive social connectedness.